2018
DOI: 10.1007/s10439-018-2089-4
|View full text |Cite
|
Sign up to set email alerts
|

Region-Specific Microstructure in the Neonatal Ventricles of a Porcine Model

Abstract: The neonate transitions from placenta-derived oxygen, to supply from the pulmonary system, moments after birth. This requires a series of structural developments to divert more blood through the right heart and onto the lungs, with the tissue quickly remodelling to the changing ventricular workload. In some cases, however, the heart structure does not fully develop causing poor circulation and inefficient oxygenation, which is associated with an increase in mortality and morbidity. This study focuses on develo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 40 publications
(60 reference statements)
4
13
0
Order By: Relevance
“…It is expected that there are differences in myofibre structure between the porcine heart and the canine heart, but this is difficult to assess as we do not have measured DT-MRI fibre structure for the porcine heart. However, despite the species difference, we find that the mapped canine myofibre structure agrees well with other studies in terms of mean values [6,23,25] (table 1). For instance, Ahmad et al [25] measured myofibre rotation angles in LV free wall of neonatal hearts (anterior 51.1 ± 3.8°to −51.1 ± 3.8°and posterior 40.2 ± 2.9°to −40.2 ± 2.9°).…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…It is expected that there are differences in myofibre structure between the porcine heart and the canine heart, but this is difficult to assess as we do not have measured DT-MRI fibre structure for the porcine heart. However, despite the species difference, we find that the mapped canine myofibre structure agrees well with other studies in terms of mean values [6,23,25] (table 1). For instance, Ahmad et al [25] measured myofibre rotation angles in LV free wall of neonatal hearts (anterior 51.1 ± 3.8°to −51.1 ± 3.8°and posterior 40.2 ± 2.9°to −40.2 ± 2.9°).…”
Section: Discussionsupporting
confidence: 91%
“…However, despite the species difference, we find that the mapped canine myofibre structure agrees well with other studies in terms of mean values [6,23,25] (table 1). For instance, Ahmad et al [25] measured myofibre rotation angles in LV free wall of neonatal hearts (anterior 51.1 ± 3.8°to −51.1 ± 3.8°and posterior 40.2 ± 2.9°to −40.2 ± 2.9°). Sack et al [6] reported fibre rotation angles for a normal adult porcine heart based on DT-MRI measurements (endocardium: 66.5 ± 16.6°, epicardium: −37.4 ± 22.4°).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Sacks et al reported that the canine RV had greater anisotropy than the LV [17]. Similarly, Ahmad et al found that the neonatal porcine RV had significantly greater anisotropy than the LV in different anatomic regions [89]. However, Javani et al reported that the ovine LV was more anisotropic than the RV [44].…”
Section: Anisotropic Behavior Of Ventriclesmentioning
confidence: 99%
“…Micro-structurally informed constitutive modelling in soft tissue has attracted tremendous interest in this area since its introduction in the 1970s [7]. With advanced imaging techniques, such as diffusion tensor magnetic resonance imaging, detailed three-dimensional (3D) fibre distribution for the whole organ, such as the heart, can be acquired in ex/in vivo [8,9]. Existed measurements have shown that fibres in myocardium are dispersed in space with a predominant mean fibre direction [8,10].…”
Section: Introductionmentioning
confidence: 99%